The correlation between some immunological parameters and causative agent in patients with otitis media - Althahab, Azhar; Abdul-Majeed, Khulood; Hameed, Wasan; Hathal, Wurood (Pharmakeftiki, 2025)
Otitis media, an inflammation of the middle ear, is a common illness in both childhood and adulthood. It arises due to various factors, primarily microbiological and immunological. This study aimed at investigating the microorganisms and fungi associated with otitis media in Iraqi patients, as well as to examine the correlation between causative agents (bacteria and fungi). The study was conducted between November 2017 and April 2018 at the Al-Hilla Teaching Hospital in Babylon City. A total of 90 pus and blood samples were collected from patients aged 1–80 years with otitis media. Samples were taken from discharging ears using sterile transport medium swabs. Of the 90 samples, 86 (95.6%) tested positive for microbial agents, while 4 cases (4.4%) had no identifiable causative agent. Among the infected individuals, 57 were male (63.3%) and 33 were female (36.7%). Samples were analysed in the microbiology laboratory in order to identify microbial species responsible for otitis media. The highest infection rates were observed in the age groups 1–20 years (34.4%) and 41–60 years (32.2%). Immunological parameters from the patients’ sera revealed significant differences compared to those of the control group (N=20). While C-reactive protein levels showed no significant difference between patients and controls, serum interleukin-10 concentrations were found to be significantly elevated in patients with bacterial infections.